Sky-like interior light settings: a preference study - Klir, Stefan; Babilon, Sebastian; Myland, Paul; Benkner, Simon; Khanh, Tran Quoc (Frontiers in Built Environment, 2023)
This paper explores human observer preferences for various sky-like interior lighting scenarios realized by a combination of a blue-enriched indirect uplight component with a correlated color temperature (CCT) of 6,500 K up to 30,000 K and a 4,000 K or 5,500 K direct downlight component. Variations in the natural sky were mimicked by the indirect uplight component reflected from the ceiling of the experimental room. The settings for the direct lighting component, on the other hand, were selected based on the reported outcomes of previous preference studies in the field of interior lighting. The resulting lighting conditions were evaluated by a total of 29 observers, from which subjective ratings of brightness, sky-likeness, satisfaction, pleasantness, and general appeal were collected in an office workplace environment. In this experimental setting, the most preferred lighting conditions exhibited a direct-to-indirect lighting ratio of 50:50 with a CCT of 4,000 K in the direct component and 6,500, 7,500, and 9,000 K in the indirect component. For all examined combinations, none was rated as truly sky-like. Nonetheless, the study results showed that only the combination of a warmer CCT in the direct component and a cooler, blue-enriched CCT in the indirect lighting component leads to a maximum in the subjects’ preference ratings. In summary, the subjects preferred light settings with a white appearance on the work surface without any intense or noticeable blue cast or tint.